Sex and gender approaches in environmental health research: two exemplary case studies of the German environment agency. (3rd April 2019) - Dębiak, Małgorzata; Groth, Katrin; Kolossa-Gehring, Marike; Sauer, Arn; Tobollik, Myriam; Wintermeyer, Dirk
ABSTRACT: Engaging with the analytical categories of sex and gender in environmental health studies remains challenging in practice but promising with regards to research excellence and scientific benefit. The German Environment Agency reports on two case studies navigating this complex interaction in the fields of health risk assessment of environmental stressors and human biomonitoring studies. It is apparent that the levels of integration of the sex/gender theories and sex/gender data are differently advanced in research. In some areas the collection of sex-disaggregated data has just begun, whereas in others research started engaging with newer gender theories such as embodiment or intersectionality. The practical applications and obstacles in incorporating sex and gender dimensions into environmental health studies are presented and discussed.